The new fiscal federalism and the social safety net : a view from California - Hosek, James R.; Levine, Robert A.; Rand Corporation; Fiscal Federalism (1996 : Santa Monica, Calif.) (Santa Monica, CA : RAND, 1996)
These essays review the implications of the new fiscal federalism for the states, particularly California, from the perspective of intergovernmental relations, fiscal impact, program administration, and the consequences for the public. Topics include AFDC, child care, child protection, Medicaid, job training, and the impact of prospective federal funding cuts on the California state budget. An introduction by the editors provides an overview of the issues, the nature of proposed policy changes, and their effects. The papers were given at a May 1996 RAND conference and revised to incorporate the observations of state, local, and county officials who participated in the two-day event.
Includes bibliographical references (p. 185).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Block grants -- California; Federal aid to public welfare -- California; Public welfare -- California -- Finance